The anatomy of the Nuremberg trials : a personal memoir - Taylor, Telford (Knopf, 1992)
Nuremberg and the laws of war -- The Nuremberg ideas -- Justice Jackson takes over -- Establishing the court: the London Charter -- The defendants and the charges: Krupp and the German General Staff -- Berlin to Nuremberg -- Nuremberg: pretrial pains and problems -- On trial -- The Nuremberg War Crimes Community -- The SS and the general staff-high command -- Individual defendants, future trials, and criminal organizations -- The French and Soviet prosecutions -- The defendants: Goering and Hess -- The defendants: "Murderers' row" -- The defendants: bankers and admirals -- The defendants: the last nine -- The closing arguments -- The indicted organizations -- The defendants' last words -- The judgments of Solomons -- Judgement: law, crime, and punishment -- Epilogue and assessment